Testing the Effectiveness of an Ecomedia Literacy Environmental Education Lesson - Ludovica Lo Iacono; Antonio López; Emilio Paolo Visintin (Social Sciences, 2024)
The growing environmental crisis requires innovative educational strategies to promote pro-environmental attitudes and behaviors. In this context, ecomedia literacy, which combines ecological education and media to enhance pro-environmental attitudes and behaviors, stimulate sustainable actions, and foster critical thinking, represents a promising approach. In this research, we evaluated the effectiveness of an ecomedia literacy-based lesson. Participants (N = 106) were randomly assigned to either an ecomedia literacy group or a control group. Those in the ecomedia literacy group first attended the lesson and then completed a questionnaire to assess pro-environmental attitudes and behavioral intentions, while those in the control group completed the questionnaire before the lesson. The lesson focused on the use of plastic water bottles, and attitudes and intentions were assessed both in general toward the environment and specifically regarding the consumption of plastic bottles. The intervention was not successful in changing intentions or attitudes toward plastic bottles, but some facets of pro-environmental attitudes were better in the ecomedia literacy group than in the control group. The limited effectiveness of the lesson indicates the need for significant changes in content and future strategies to better achieve sustainability goals.